KIDMED 2.0, An update of the KIDMED questionnaire: Evaluation of the psychometric properties in youth - López-Gajardo, Miguel A.; Leo, Francisco M.; Sánchez-Miguel, Pedro Antonio; López-Gajardo, Dori; Soulas, Candelaria; Tapia-Serrano, Miguel A. (Frontiers in Nutrition, 2022)
Background & aims: As children and adolescents´ eating patterns have changed over the last few years, researchers have found inconsistencies in the current questionnaires. Therefore, this research aims to i) update the 2019 KIDMED questionnaire; and ii) test the psychometric properties of this new questionnaire. Method: A study with 419 children and adolescents in southwestern Spain was conducted in 2021. The new version of the KIDMED 2.0 was tested, which measures adherence to the Mediterranean diet through 16 items, of which 12 are positive, and 4 are negative. Content validation involved consultation with nutritionists, experts, and adolescents to assess whether the questionnaire was reliable and valid regarding dietary patterns associated with the Mediterranean diet. The expert assessment provided content validity indices for the clarity and representativeness of the questionnaire. Construct validity and test-retest reliability involved 419 students (Mage = 14.40 ± 2.00) from southwestern Spain. Students responded twice (one week apart) to the KIDMED developed in the previous stage and completed a 7-day dietary record. Results: Regarding validity, results show a moderate agreement for 10 items (ranging between .21 and .47) of the KIDMED and the 7-day dietary record. Concerning Items 3, 4, 5, and 6, the agreement was slight (ranging between .08 and .17), whereas the agreement for Item 8 was low. Cohen’s kappa showed that most items had moderate to substantial test-retest reliability. Also, kappa showed significant test-retest values for all items (p < .001). Conclusion: The new version of the KIDMED 2.0 was shown to be a reliable and valid instrument to measure adherence to the Mediterranean diet in children and adolescents.